Layered directionally-arranged boron nitride ceramic as well as preparation method and application thereof
The graphite template method alternately scraping inorganic adhesive and boron nitride powder and processing at high temperatures solved the problem of the mechanical properties of ceramic materials affected when temperature changes, and prepared a sheet-like layer with excellent high-temperature oxidation resistance and stable mechanical properties Directional arrangement of boron nitride ceramics, suitable for aerospace fields.
Patent Information
- Application Number
- CN202411588989.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-08
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-11-08
AI Technical Summary
The mechanical properties of existing ceramic materials are greatly affected when temperature changes, and are difficult to prepare, expensive to build, and have poor design results.
Using graphite as the template method, the inorganic glue and boron nitride powder were alternately scraped and heated at high temperature to remove the graphite matrix, and the sheet-like orientation-arranged boron nitride ceramic was prepared.
The prepared ceramics have low dielectric, good oxidation resistance, and their mechanical properties vary less with temperature. They are suitable for cutting-edge radome materials in the aerospace field.
Smart Images

Figure CN119462164A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of boron nitride ceramic preparation, and in particular relates to a lamellar oriented boron nitride ceramic and a preparation method and application thereof. Background Art
[0002] The rapid development of the contemporary aviation field has aroused considerable interest in materials related to various applications such as the radomes at the tip of fighter jets. The materials for fighter jet radomes need to have low dielectric constant, good oxidation resistance, and small changes in mechanical properties with temperature. However, due to the mismatch of thermal expansion coefficients between materials, the structures of many ceramic materials are clamped by internal thermal stress, resulting in their mechanical properties being greatly affected by temperature. The preparation research of such materials has always been in a state of difficult preparation, high cost, and poor design effect.
[0003] Therefore, there is an urgent need to provide a method for preparing lamellar oriented boron nitride ceramics. Summary of the invention
[0004] In view of the above technical problems, the present invention proposes a lamellar oriented boron nitride ceramic and its preparation method and application. The present invention innovatively proposes a template method using graphite as the matrix of lamellar oriented boron nitride ceramics, and uses high-temperature heating to fully oxidize the graphite matrix to obtain an undamaged lamellar oriented boron nitride ceramic, whose mechanical properties change little with temperature. The preparation method is simple, the raw materials are cheap, and it is conducive to large-scale production. Therefore, the present invention discloses a method for preparing lamellar oriented boron nitride ceramics using a template method, and explores the mechanism of the evolution of microstructure and mechanical properties with temperature, as well as the intrinsic relationship between thermal stress and crystal orientation, and designs the microscopic crystal arrangement of the material to improve the mechanical properties of the material.
[0005] To achieve the above object, the present invention provides the following technical solutions:
[0006] One of the technical solutions:
[0007] A method for preparing lamellar oriented boron nitride ceramics by using a template method comprises the following steps:
[0008] By using the template method, a carbonaceous material graphite with a flat surface is used as a matrix, and inorganic glue and boron nitride powder are alternately scraped on its surface, and then heated to prepare lamellar oriented boron nitride ceramics.
[0009] Beneficial effects: The present invention uses graphite as a matrix and adopts a scraping method to synthesize lamellar oriented boron nitride ceramics on the surface of the matrix material. The prepared lamellar oriented boron nitride ceramics have the advantages of low dielectric constant, good oxidation resistance, and small variation in mechanical properties with temperature.
[0010] In addition, according to the template method design concept proposed in the present invention, after the inorganic glue and boron nitride powder are scraped and dried on the graphite substrate multiple times, the graphite substrate can be oxidized by high-temperature heating treatment, thereby achieving the purpose of removing the substrate and obtaining a directional boron nitride ceramic.
[0011] Preferably, the inorganic colloidal solvent includes aluminum phosphate and / or sodium silicate.
[0012] Beneficial effects: The inorganic glue (sodium silicate or aluminum phosphate colloid) defined in the present invention can play the role of low-temperature adhesion and high-temperature curing. Specifically: its high viscosity and strong wettability at low temperature are conducive to the rotation of boron nitride powder (h-BN powder) through scraping, thereby facilitating its single-direction arrangement; after heating, the inorganic glue can achieve the connection between BN layers through dehydration polymerization, thereby enhancing the stability between ceramic matrix layers.
[0013] Preferably, the mass fraction of the solute is 30-80%.
[0014] Preferably, the type of boron nitride in the boron nitride powder is h-BN.
[0015] Preferably, the specific operation of alternating scraping is:
[0016] First, a layer of inorganic glue is scraped on the graphite surface, and then a layer of boron nitride powder is applied. The obtained sample is cured, and this is a complete cycle.
[0017] Preferably, the usage ratio of the graphite, the inorganic glue and the boron nitride powder is 20:1:10.
[0018] Preferably, the temperature during the curing process is 80-200°C.
[0019] Preferably, the number of cycles is 50-100 times.
[0020] Preferably, the heating process is:
[0021] Raise the temperature to 500-900°C and then keep at this temperature for 10 hours.
[0022] Technical solution 2:
[0023] The preparation method mentioned above prepares a lamellar oriented boron nitride ceramic.
[0024] Technical solution three:
[0025] The above-mentioned lamellar oriented boron nitride ceramics are used in the aerospace field.
[0026] Compared with the prior art, the present invention has the following advantages and technical effects:
[0027] The template method for preparing lamellar oriented boron nitride ceramics provided by the present invention has high stability, strong controllability, simple preparation steps, cheap and readily available raw materials, and is conducive to large-scale production.
[0028] The lamellar oriented boron nitride ceramics prepared by the preparation method of the present invention can be used in aerospace fields such as fighter aircraft tip antenna covers, and have excellent high-temperature oxidation resistance and small changes in mechanical properties with temperature. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] The drawings constituting a part of the present application are used to provide a further understanding of the present application. The illustrative embodiments and descriptions of the present application are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:
[0030] Figure 1 Scanning images of the surface and cross section of the boron nitride ceramic prepared in Example 1 of the present invention;
[0031] Among them, (a) and (b) are surface scans; (c) and (d) are cross-sectional scans. DETAILED DESCRIPTION
[0032] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0033] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0034] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0035] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.
[0036] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0037] The invention discloses a method for preparing lamellar oriented boron nitride ceramics by using graphite as a matrix template, comprising the following steps:
[0038] 1) Alternately scrape the inorganic glue and boron nitride powder onto the surface of the graphite block;
[0039] 2) drying and curing the inorganic glue and boron nitride;
[0040] 3) Repeat the scraping and drying to solidify, and subject the obtained sample to high-temperature heating and heat preservation treatment to obtain lamellar oriented boron nitride ceramics.
[0041] In some preferred embodiments of the present invention, the mass fraction of the solute in the inorganic glue in step 1) is 30-80%, preferably 50%.
[0042] Inorganic colloidal solvents include aluminum phosphate and sodium silicate; aluminum phosphate is preferred.
[0043] In some preferred embodiments of the present invention, the drying temperature after each alternating scraping of the inorganic glue and the BN powder in step 3) is in the range of 80-200°C, preferably 200°C.
[0044] The number of repeated scraping and drying curing is in the range of 50-100 times, preferably 70 times.
[0045] The temperature range of the high temperature heating treatment is 500-900°C, preferably 800°C.
[0046] The present invention uses graphite as a matrix, and through the mechanism of oxidation reaction at high temperature, the template can be easily removed to obtain oriented boron nitride ceramics. The template method has wide applicability and can be used in different research contents, which provides a new idea for the preparation of ceramic materials. At the same time, the material preparation method is simple, the raw material price is low, and it is easy to apply on a large scale.
[0047] The principle of the invention is that after the lamellar structure shrinks or expands due to temperature, the mechanical properties change little in the direction perpendicular to the lamellar layer and parallel to the lamellar layer. This effectively solves the problem that the thermal expansion coefficients of the heated materials do not match each other, and that the mechanical properties of many ceramic materials and other structures are greatly affected by temperature due to the clamping effect of internal thermal stress.
[0048] The preparation method disclosed in the present invention can be used to prepare lamellar oriented boron nitride ceramics. The ceramics have excellent high-temperature oxidation resistance and small changes in mechanical properties with temperature, and can be used in aerospace fields such as fighter aircraft cutting-edge radome materials.
[0049] The "room temperature" in the present invention refers to 20-30°C unless otherwise specified.
[0050] The raw materials used in the present invention are all purchased from the market.
[0051] The technical solution of the present invention is further illustrated by the following embodiments.
[0052] Example 1
[0053] A method for preparing lamellar oriented boron nitride ceramics by using a template method comprises the following steps:
[0054] 1) Alternately scrape a 50% aluminum phosphate solution and h-BN powder onto the surface of the graphite block, first apply the aluminum phosphate solution, then apply the h-BN powder, wherein the coating amount of each layer of aluminum phosphate solution and h-BN powder is 0.1g and 1g respectively;
[0055] 2) drying and curing the graphite block after the coating at a temperature of 200° C. to a constant weight;
[0056] 3) Repeat the above-mentioned scraping and drying steps 70 times, and heat the obtained sample at a temperature of 800° C. for 10 hours to fully oxidize the graphite block and remove the graphite block to obtain a lamellar oriented boron nitride ceramic.
[0057] Figure 1 These are scans of the surface and cross-section of the boron nitride ceramic prepared in Example 1 of the present invention; wherein, (a) (b) are surface scans, from which it can be seen that the boron nitride is distributed and superimposed in lamellar form as a whole, the lamellar structure can be clearly observed, and the boron nitride is distributed evenly; (c) (d) are cross-sectional scans, from which the distribution direction of the boron nitride lamellar layers can be observed.
[0058] Example 2
[0059] Same as Example 1, except that the aluminum phosphate solution in step 1) is replaced by a sodium silicate solution.
[0060] Example 3
[0061] Same as Example 1, except that the mass fraction of the aluminum phosphate solution in step 1) is adjusted to 30%.
[0062] Example 4
[0063] Same as Example 1, except that the drying temperature in step 2) is adjusted from 200°C to 80°C.
[0064] Example 5
[0065] Same as Example 1, except that the number of repeated scraping and drying steps in step 3) is adjusted to 100 times.
[0066] Example 6
[0067] Same as Example 1, except that the temperature of the high temperature heating treatment in step 3) is adjusted to 900°C.
[0068] Comparative Example 1
[0069] Same as Example 1, except that the h-BN powder in step 1) is replaced by SiO2.
[0070] The results showed that the structure of SiO2 is not a simple lamellar structure, but a three-dimensional network structure formed by silicon-oxygen tetrahedron as the basic structure. During the preparation process, it is impossible to obtain SiO2 ceramics with directional arrangement.
[0071] Comparative Example 2
[0072] Same as Example 1, except that the mass fraction of the aluminum phosphate solution in step 1) is adjusted to 25%.
[0073] The results showed that the aluminum phosphate solution was too dilute, which resulted in poor adhesion of the h-BN powder and difficulty in forming a film on the surface of the graphite block.
[0074] Comparative Example 3
[0075] Same as Example 1, except that the mass fraction of the aluminum phosphate solution in step 1) is adjusted to 85%.
[0076] The results showed that because the aluminum phosphate solution was too thick, it was difficult to evenly apply the BN powder on the surface of the graphite block and it was not easy to form a smooth surface.
[0077] Comparative Example 4
[0078] Same as Example 1, except that the temperature of the high temperature heating treatment in step 3) is adjusted to 1300°C.
[0079] The results showed that excessively high heating temperature caused some BN ceramics to be oxidized, the planar structure to be destroyed, and defects to occur, which affected the subsequent mechanical properties testing.
[0080] Comparative Example 5
[0081] Same as Example 1, except that the temperature of the high temperature heating treatment in step 3) is adjusted to 300°C.
[0082] The results showed that the heating temperature was too low, resulting in incomplete oxidation of the graphite block, and the graphite block could not be completely eliminated, and the prepared lamellar oriented boron nitride ceramics could not be removed from the graphite block.
[0083] Effect verification
[0084] (I) The ceramics prepared in Examples 1-6 and Comparative Examples 1-5 were tested for three-point bending resistance in two directions, vertical and parallel to the plane. The samples were prepared into 40×4×3mm strips in two stress directions, with a span of 30mm and a loading speed of 0.5mm / min, to verify the effect of variable temperature mechanical (thermal stress) performance. The relevant effect data are shown in Tables 1 and 2 below.
[0085] Table 1 Vertical plane direction
[0086]
[0087]
[0088] Table 2 Parallel plane directions
[0089]
[0090] It can be seen from the above table that when external pressure is applied to the silicon nitride ceramics prepared in Examples 1-6 of the present invention from both the vertical plane direction and the parallel plane direction, the mechanical properties change little with temperature during the process of heating from room temperature to 800°C, and the silicon nitride ceramics are suitable for aerospace materials such as the antenna cover at the tip of a fighter jet.
[0091] (II) The ceramics prepared in Examples 1-6 and Comparative Examples 1-5 were subjected to high temperature oxidation tests at temperatures of 800, 1000, and 1300° C., respectively, and the oxidation time was 10 min. Specific data are shown in Table 3.
[0092] Table 3 Weight loss rate before and after oxidation
[0093]
[0094] The above are only preferred specific implementations of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.
Claims
1. A method for preparing lamellar oriented boron nitride ceramics by using a template method, characterized in that: The following steps are involved: The template method is used to prepare lamellar oriented boron nitride ceramics by taking graphite as the matrix, coating the surface of the graphite with inorganic glue and boron nitride powder alternately, and heating the graphite.
2. The method for preparing lamellar oriented boron nitride ceramics by template method according to claim 1, characterized in that: The inorganic colloidal solute includes aluminum phosphate and / or sodium silicate; wherein the mass fraction of the solute is 30-80%.
3. The method for preparing lamellar oriented boron nitride ceramics by template method according to claim 1, characterized in that: The boron nitride powder is hexagonal boron nitride.
4. The method for preparing lamellar oriented boron nitride ceramics by template method according to claim 1, characterized in that: The specific operation of the alternating scraping is as follows: A layer of inorganic glue is firstly scraped on the graphite surface, and then a layer of boron nitride powder is applied, and the obtained sample is cured, and this is regarded as a complete cycle of cyclic scraping.
5. The method for preparing lamellar oriented boron nitride ceramics by template method according to claim 4, characterized in that: In each cycle, the mass ratio of the inorganic glue to the boron nitride powder applied is 1:
10.
6. The method for preparing lamellar oriented boron nitride ceramics by template method according to claim 4, characterized in that: The temperature during the curing process is 80-200°C.
7. The method for preparing lamellar oriented boron nitride ceramics by template method according to claim 4, characterized in that: The number of cycles is 50-100 times.
8. The method for preparing lamellar oriented boron nitride ceramics by template method according to claim 1, characterized in that: The heating process is: Raise the temperature to 500-900°C and then keep at this temperature for 10 hours.
9. A lamellar oriented boron nitride ceramic, characterized in that: The method is prepared by any one of claims 1 to 8.
10. Application of the lamellar oriented boron nitride ceramics according to claim 9 in the field of aerospace.
Citation Information
Patent Citations
Method for preparing high-orientation heat conduction h-BN-based ceramic material based on 3D printing technology
CN112358300A
Preparation method of highly-oriented horizontally-arranged boron nitride film
CN116651720A
Enhanced heat diffusion and heat dissipation carbon-based composite film and manufacturing method thereof
CN116685111A
Ceramic member and its producing method
JP2006182587A
Method of forming in-situ boron nitride for ceramic matrix composite environmental protection
US20150284295A1